2004
DOI: 10.1080/1367626042000315194
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness, Gender and Subsistence: The Case of Toronto Street Youth

Abstract: Research on employment segregation and women's lower earnings has predominantly focused on labour-market participants. Marginal groups such as the homeless have therefore been excluded from theory and research on work-related gender segregation. In order to ®ll this void, this paper explores how income creation among homeless youth from Toronto, Canada varies according to gender. Based on questionnaire and interview data our results show that, in relative terms, males are involved in the more ®nancially lucrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 23 publications
(24 reference statements)
1
87
0
6
Order By: Relevance
“…They may enter into an intimate relationship exchanging sex for shelter, which, for women, often introduces or stabilises a gendered power imbalance. 15 Sex workers are forced to work in public spaces, which has been shown to be associated with an increased risk of coercive unprotected sex. 16 A substantial number of participants engaged in sex work.…”
Section: Resultsmentioning
confidence: 99%
“…They may enter into an intimate relationship exchanging sex for shelter, which, for women, often introduces or stabilises a gendered power imbalance. 15 Sex workers are forced to work in public spaces, which has been shown to be associated with an increased risk of coercive unprotected sex. 16 A substantial number of participants engaged in sex work.…”
Section: Resultsmentioning
confidence: 99%
“…In one study of 207 homeless or previously homeless youth in California, 75 % of youth reported regular and negative interactions with police (Bernstein and Foster 2008). Although street-involved youth are more likely to be involved in criminal activity than domiciled youth, O'Grady and Gaetz (2007) point out that while crimes are more likely to be committed by male youth, "theft and drug dealing are by no means dominant money-making activities". In the aforementioned California study, only 8 % of youth reported getting money from theft, 7 % from selling drugs, and 5 % from prostitution (Bernstein and Foster 2008).…”
Section: Who Are Street-involved Youth?mentioning
confidence: 97%
“…Elles vont taire leur situation, par peur de perdre ou de ne pas récupérer la garde de leurs enfants, mais aussi par peur du jugement des autres (Corwal, 2002 ;Sznajder-Murray et Slesnick, 2011 ;Zlotnick, Tam et Bradley, 2010). Dans la rue, elles vont adopter des stratégies de survie particulières pour se prémunir des violences physiques et sexuelles : se procurer un chien (Jamoulle, 2009) ; cesser de se laver 3 ; adopter une attitude agressive et masculine (Huey et Berndt, 2008) ; établir des relations intimes homosexuelles (Bellot, 2001) ; avoir recours à un proxénète (O'Grady et Gaetz, 2004) ; ou s'unir à un homme pour en tirer une forme de protection (Jamoulle, 2009 ;Lanzarini, 2000 ;Osthus et Sewpaul, 2014 ;Watson, 2011). Les relations intimes permettent ainsi aux femmes d'obtenir une sécurité émotionnelle, physique et matérielle (Kirst, Erickson et Strike, 2009 ;Raffaelli et al, 2000 ;Watson, 2013) et, dans certains cas, d'améliorer leurs conditions de vie (Laporte, Le Ménier, Oppenchaim, Pourette et Carpentier, 2007).…”
Section: La Production De L'itinérance : De L'identification Des Factunclassified